984A novel cost diary approach to analyse the financial burden of living with arthritis. (2nd September 2021) - Berkovic, Danielle; Ayton, Darshini; Briggs, Andrew; Ackerman, Ilana
Abstract: Focus of Presentation: Amongst Australia's working-age population with arthritis, financial distress is known to be high and contribute to poorer health outcomes. Yet the personal financial burden of living with arthritis is not well understood. Here we present initial findings from one of the first projects to measure personal financial distress as a determinant of health for individuals living with arthritis. Findings: Participants aged 18-50 years detailed their arthritis-attributable out-of-pocket costs in an online consumer-informed cost diary; once a week, for six weeks, alongside a work productivity and financial distress scale. Costs were grouped into seven categories, including: direct medical appointments, allied health appointments, other health appointments, medications or supplements, symptom/pain management items, medical tests, and other expenses. Costs per individual per week ranged from 40.30 (AUD) to 25, 789 (AUD). High costs were not linked to quality of care, demonstrated by one participant spending 495.00 (AUD) on chiropractic appointments across the six weeks. High levels of financial distress were associated with reduced work productivity, but were not associated with level of weekly expenditure. Conclusions/Implications: Adults with arthritis experience financial hardship associated with their disease. Discussion of arthritis-related financial concerns should form part of shared clinical decision-making and education, to facilitate prioritisation of care that is evidence-based and feasible. Key messages: These findings can be used to raise awareness of key fiscal issues relevant to adults with arthritis, and to educate clinicians about the wide-ranging impacts of arthritis beyond physical symptoms.